Preparation of PHEMA/TiO2 nanocomposites by combination of in-situ polymerization/hydrothermal method and determination of their thermal, swelling, biological and dielectric properties - Erol, Ibrahim; Yurdakal, Sedat; Demirelli, Kadir; Gurler, Zeki (Springer, 2022)
Poly(2-hydroxyethyl methacrylate) (PHEMA) and TiO2 nanoparticles (NPs) containing polymeric nanocomposites (PNCs) in different mass ratios of TiO2 (3, 5 and 7%) with respect to PHEMA were synthesized by using the in-situ polymerization/hydrothermal method. The prepared composite materials were characterized by SEM, FTIR, UV-Vis, TGA and XRD techniques. The results of the characterization experiments showed that the composite successfully synthesized and TiO2 in the polymer matrix is well distributed, especially for the lowest TiO2 contained composite (3% TiO2). The thermal activation energies (E-a) of the PNCs were estimated by the Ozawa, Kissinger, and Kissinger-Akahira-Sunose methods by using non-isothermal TGA experiments. By increasing the amount of TiO2 nanoparticles, the thermal stability and glass transition temperature (T-g) of PHEMA was increased. The water holding capacity of PNCs was determined by swelling experiments. As the amount of TiO2 in the PNCs increased, the degree of swelling decreased. In addition, the swelling values of both PHEMA and PNCs increased with increasing the temperature. The dielectric constant (sigma '), the dielectric loss factor (sigma '') and ac conductivity of neat PHEMA and PNCs were also measured for the frequency range of 100 Hz to 2 kHz and for the temperatures of 30 and 180 degrees C. It was obtained that the frequency dependence of the dielectric constant and dielectric loss factor decreased with increasing frequency. Finally, the biological activities of PNCs against gram-positive (S. aureus) and gram-negative (E. coli) bacteria were also tested and it was observed that this effect increased with the amount of TiO2.
Keywords: PHEMA; TiO2 composite; In-situ polymerization; hydrothermal method; Thermal decomposition kinetics; Antimicrobial activity; Swelling properties; Dielectric properties